Antiviral mechanism of polyanionic carbosilane dendrimers against HIV-1 - Vacas-Córdoba, Enrique; Maly, Marek; De la Mata, Francisco J; Gómez, Rafael; Pion, Marjorie; Muñoz-Fernández, M Ángeles (International journal of nanomedicine, 2016)
Nanotechnology-derived platforms, such as dendrimers, are very attractive in several biological applications. In the case of human immunodeficiency virus (HIV) infection, polyanionic carbosilane dendrimers have shown great potential as antiviral agents in the development of novel microbicides to prevent the sexual transmission of HIV-1. In this work, we studied the mechanism of two sulfated and naphthylsulfonated functionalized carbosilane dendrimers, G3-S16 and G2-NF16. They are able to inhibit viral infection at fusion and thus at the entry step. Both compounds impede the binding of viral particles to target cell surface and membrane fusion through the blockage of gp120-CD4 interaction. In addition, and for the first time, we demonstrate that dendrimers can inhibit cell-to-cell HIV transmission and difficult infectious synapse formation. Thus, carbosilane dendrimers' mode of action is a multifactorial process targeting several proteins from viral envelope and from host cells that could block HIV infection at different stages during the first step of infection.
Keywords: HIV-1; dendrimery; replikace viru; HIV Infections; silany; HIV Envelope Protein gp120; antivirové látky; Dendrimers; Polymers; HIV infekce; fúze membrán; molekulární modely; Membrane Fusion; Models, Molecular; Antiviral Agents; lidé; polymery; Virus Replication; Humans; Silanes; HIV obalový protein gp120